KEBERHASILAN PINDAH TANAM SETEK CABANG BAMBU AMPEL HIJAU (Bambusa vulgaris) DARI KULTUR AIR KELAPA - Sandra Arifin Aziz (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
An experiment of transplanting one and two nodes of green Bambusa vulgaris branch cutting from water culture the field was carried out with the application of chicken manure 0.0, 0.2, 0.4, 0.6, and 0.8 kg/plantlet, with based fertilizer Urea, TSP, and KCl 0.50, 0.50, and 0.50 kg/plantlet, respectively. Split plot design was used, with chicken manure as main plot and number of nodes as sub plot. All the combination were replicated thrice. Chicken manure 0.4 kg and Urea 0.50, TSP 0.25 and KCl 0.50 kg/plantlet is relatively needed to transplant green Bambusa vulgaris branch cutting from water culture to the field. Plantlet with two nodes had better growth ability than one nodes on 12 and 14 weeks after transplanting, although no significant differences observed at the initial and the end of the experiment.